Assessment of the stability of citrate-buffered piperacillin/tazobactam for continuous infusion when stored in two commercially available elastomeric devices for outpatient parenteral antimicrobial chemotherapy: a study compliant with the NHS Yellow Cover Document requirements. Issue 4 (25th September 2020) - Jamieson, Conor; Ozolina, Laima; Seaton, R Andrew; Gilchrist, Mark; Hills, Tim; Drummond, F; Wilkinson, Alan Shaun
Abstract : Objectives: To investigate the effect of pH control through the use of a citrate-buffered saline diluent pH 7 on the degradation rate of piperacillin/tazobactam solutions for infusion and to determine if an extended shelf-life of up to 13 days fridge 2°C–8°C plus 24 hours 'in-use' at 32°C in two elastomeric devices: FOLFusor LV10 (Baxter Healthcare, Thetford, UK) and Easypump II (B. Braun Medical Ltd, Sheffield, UK) can be achieved. Methods: Testing was as per the latest National Health Service (NHS) Pharmaceutical Quality Assurance Committee Yellow Cover Document (YCD) requirements. A validated stability indicating high-performance liquid chromatography method was used for assessing the stability of the solutions of piperacillin/tazobactam at a combined concentration of 25 mg/mL and 90 mg/mL respectively. Solutions were tested in two batches in replicate (n=3) at five time points according to the requirements of the YCD. Results: Piperacillin/tazobactam stability was significantly improved when 0.3% w/v citrate-buffered saline pH 7 was used as the diluent, compared with using 0.9% w/v saline as diluent. Greater than 95% of the zero-time concentration of both actives remained following storage at 2°C–8°C for up to 13 days plus 24 hours at 32°C in both devices. The data support extended storage of up to 13 days 2°C–8°C plus 24 hours at 32°C 'in-use' when using FOLFusor LV10 (Baxter) or Easypump II (B. Braun) pump devices. Conclusions: The enhanced stability complies with UK national standards as stated in the YCD for stability testing of aseptically produced small molecules and supports the storage of piperacillin/tazobactam for up to 13 days 2°C–8°C plus 24 hours at 32°C 'in-use' within two elastomeric pump devices. The extended shelf-life provides a significant advantage over the stability of piperacillin/tazobactam solutions for infusion when reconstituted and diluted in 0.9% w/v saline as diluent. The data open up the possibility of a continuous infusion of piperacillin/tazobactam delivered by elastomeric pump devices over 24 hours in an outpatient parenteral antimicrobial therapy setting.